Pleural manometry during thoracocentesis in patients with malignant pleural effusion: A randomized controlled trial - Aly Sherif Hassaballa; Ahmed Mostafa; Tamer Hikal; Ahmed Elnori; Hany Hasan Elsayed (Canadian Journal of Respiratory Therapy, 2023)
Background: Large-volume therapeutic thoracocentesis may be associated with pulmonary congestion or a more serious complication; re-expansion pulmonary edema (RPE). We investigated whether monitoring pleural pressure with manometry during thoracocentesis would prevent these pulmonary symptoms/RPE and allow larger volume drainage. Methods: We did a randomized controlled trial involving 110 patients with large malignant pleural effusions. Patients were randomly allocated to obtain thoracocentesis with or without pleural manometry. We measured the incidence of pulmonary congestion symptoms, total fluid aspirated, and pleural pressures in both groups. This trial is listed on ClinicalTrials.gov as NCT04420663. Results: The mean amount of total thoracocentesis fluid withdrawn from the control group was 945.4±78.9 (mL) and 1690.9±681.0 (mL) from the intervention group (P<0.001). Clinical symptoms of pulmonary congestion appeared in (n=20) (36.3%) of patients in the intervention group while no symptoms appeared in controls (P<0.001). The difference between opening and closing pressures between the non-symptomatic cluster and the symptomatic cluster was (32.8±15.6 versus 42.2±13) respectively (P=0.02). Total fluid withdrawn from the non-symptomatic cluster was 1828.5±505 mL in comparison to 1,450±875 mL in the symptomatic cluster (P=0.04). Conclusion: Pleural manometry can be used to increase the volume of fluid removed on each occasion in patients with malignant pleural effusion. In our study, pleural manometry was associated with a larger number of pulmonary congestion symptoms/RPE. We believe that manometry may be a useful tool to not exceed a 17 cm H2O gradient in pleural pressure which should be avoided to prevent pulmonary congestion symptoms or RPE. Pulmonary congestion symptoms/RPE are not related to the amount of volume withdrawn but to the gradient of pleural pressure drop. Our conclusion does support the adoption of pleural manometry whenever large-volume thoracocentesis is intended.